Integrating car rental booking system with SMS technology / Nurul Syahidah Shuhada - Shuhada, Nurul Syahidah (2020)
This paper represents the project area named as Short Messaging Service technology. It is commonly used by all people around the world since this message service application is placed not only in mobile phones, but also in smart phones. This message service technology is applicable to all users and it is affordable as it is in lower costs. This project area came out to integrate with the web-based system to solve and improve the problem that identified while having an informal interview with one of the customers of car rental in Arau. The problem occurs in car rental service around Arau where the customer and the company are involved in booking car rental procedure. However, the company needs to collect data manually and it increases the data loss and data redundancy of the company. The research focused on several objectives that are to develop a web-based system for car rental booking, integrate the web-based system SMS technology. Research methodology used to attaining some of project objectives which are using System Development Life Cycle (SDLC) methodology. The expected outcome is the car rental booking system that integrated with SMS technology. The result of usability testing and functionality testing can be concluded that the system is easy to use, the integration of system with SMS is helpful and the user satisfied to change system with current method.